Learning With Ethnomathematics Based Open Ended Approach Improves Creative Thinking Ability, Curiosity Character - Moh Saironi (Jurnal Sosial Teknologi, 2022)
Think more creatively and innovatively in dealing with problems and sites will not be possessed without extensive knowledge. This is one of the demands on all students to be able to think more creatively. the character of curiosity to be observed. The character of curiosity that will be instilled so that students have a strong self-curiosity, strength, and do not give up easily. Curiosity needs to be instilled in students through a fun approach so that students do not feel bored. Here, teachers as educators must be more creative in finding ideas to choose the right approach in developing students' curiosity. Many teachers are found using an expository model, where the teacher explains the material, provides examples and practice questions so that students are trained to do questions such as mechanics or machines. In addition, the assessment carried out emphasizes more on the final assessment and pays less attention to the process, so that mathematics learning is less meaningful; Prioritizing memorization over understanding. The purpose of this study is to examine whether learning with an Ethnomathematics-based Open Ended approach can improve students' creative thinking ability and curiosity in mathematics.  Based on the above problems, an appropriate learning approach is needed that can bridge these problems, namely learning with an Ethnomathematics-based Open Ended Learning approach, where students are given the flexibility to answer their abilities to find and develop their own knowledge. The steps begin with the awarding of a problem sourced from culture and end with analyzing and evaluating the problem-solving process. Thus, learning with an Open Ended Learning approach based on Ethnomathematics, will have a very high contribution to students' mathematical creative thinking ability and the character of students' curiosity in mathematics learning.